The effects of frontal- and sagittal-plane plyometrics on change-of-direction speed and power in adolescent female basketball players - McCormick, B. T.; Hannon, J. C.; Newton, M.; Shultz, B.; Detling, N.; Young, W. B. (International Journal of Sports Physiology and Performance, 2016)
Plyometrics is a popular training modality for basketball players to improve power and change-of-direction speed. Most plyometric training has used sagittal-plane exercises, but improvements in change-of-direction speed have been greater in multidirection programs.